Surgical outcomes of phacoemulsification with different fluidics systems (centurion with active sentry vs. centurion gravity) in cataract patients with eye axial length above 26 mm - Liu, Yinan; Chen, Xiaoyong (Frontiers in Medicine, 2025)
IntroductionDuring cataract phacoemulsification surgery, the Alcon Centurion with Active Sentry can achieve a more stable anterior chamber, which allows a lower intraocular pressure (IOP) setting than Centurion under gravity mode. In this randomized controlled trial, we compared these two systems’ impact on high myopia patients’ macular blood perfusion under different IOP settings. To evaluate intra-op and post-op clinical performance of the Alcon Centurion with Active Sentry and under gravity mode in cataract patients with eye axial lengths > 26 mm.MethodsFifty-two eyes of 43 cataract patients with axial lengths > 26 mm were enrolled and randomly divided into the active fluidics system (AFS) group using a Centurion Active Sentry handpiece under 30 mmHg IOP setting (26 eyes) and the gravity fluidics system (GFS) group in gravity mode under 80 cmH2O IOP setting (26 eyes). Intraoperative parameters, visual acuity, parafoveal macular vessel density and macular thickness were analyzed.ResultsWe observed no significant differences in best corrected visual acuity (BCVA), macular thickness, cumulative dissipated energy (CDE), total case time, as well as ophthalmic viscoelastic devices (OVDs) usage between the two groups. However, we found less pain complaints during surgeries and a more stable macular vessel density post-surgery in the AFS group than in the GFS group, implying higher intraoperative comfort levels and less retinal ischemia during cataract surgery using Centurion with Active Sentry under low IOP settings.ConclusionOwing to a lower IOP setting, Centurion Vision System with Active Sentry handpiece causes less retinal ischemia and pain perception during phacoemulsification for high myopia patients.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2400080875.